Sedimentation Assessment of Namsong Reservoir Vangvieng District Vientiane Province - souliyo, santisouk (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This study aimed to assess the amount of sediment accumulated in the Nam Song Dam reservoir, located in Vang Vieng District, Vientiane Province, using Geographic Information System (GIS) tools. The assessment focused on sediment deposition from the time of the dam’s construction in 1996 to the year 2024. The volume of sediment was estimated by comparing surface elevation data collected in 2024 with pre-construction survey data. The results showed a total sediment volume of approximately 1,125,403.42 cubic meters, averaging about 40,192.89 cubic meters per year over a 28-year period. The area of data collection covered a 3.05-kilometer stretch from the Nam Song Dam site upstream along the Nam Song River (within the reservoir boundary). The study also revealed a significant reduction in the reservoir’s water storage capacity due to sediment accumulation. Since the dam began operating in 1996, the reservoir's capacity has decreased from 13,500,000 cubic meters to 12,374,597 cubic meters in 2024 a loss of about 1,125,403.42 cubic meters. This sedimentation has resulted in an overall capacity reduction of approximately 8.34%, averaging 0.3% per year.